Maternal Mortality from a racial perspective: a narrative review (Research, Society and Development, 2021)
Racism and racial discrimination are common in Brazilian daily life and, in the area of ​​health, it can lead to negligence and compromise in the individual's physical and mental well-being and, in certain situations, it can cause death. The health of black women, and specifically of pregnant women, is not far from this when compared to the assistance that white women receive. Objectives: To identify literature with the sociodemographic profile of maternal mortality, region and main causes of death. Method: Narrative review research, qualitative analysis. It was performed in the Virtual Health Library (BVS), PubMed and Scientific Electronic Library Online (Scielo) database, through the Health Sciences Descriptors (DeCS): “Maternal mortality”, “Obstetrical Nursing”, “Health Services Maternal and Child", "Racism", "Comprehensive Health Care". Result: Of the 24 selected, only 7 bibliographies contained the variables to answer the objective of this study, with 5 coming from the northeast. A frequent death rate was identified in brown women, schooling with complete elementary school, age group from 20 to 39 and direct obstetric cause of hypertensive syndromes, while indirect causes were not specified. Conclusion: There needs to be greater investment in research on this topic due to the seriousness of the situation and the low amount of literature. It is possible that these data in the brown race are much higher than in the black race due to self-declaration, unfortunately there is still some resistance in declaring oneself black and this reflects in the data evaluated.